إعداد وحدة تعليمية من الكتب التراثية لتنمية مهارة القراءة ( بالتطبيق على مدرسة السلفية الثانوية باسروان جاوا الشرقية ) - Siti Muawanah (PPs UIN Maulana Malik Ibrahim Malang, 2010)
An appropriate lesson matter has important role to develop teaching learning process because a lesson matter represents a place of two choices between delicious foods or a bitter one that we have to give to the students. Teacher should only be a facilitator who transfers a bun of knowledge. Here, a lesson matter isn’t always seen on a right place and sometimes it doesn’t have any role if we can’t serve the best.This study is aimed to show how to arrange an appropriate lesson matter from “Kitab Kuning” to develop students reading skill in 2nd grade of Madrasah Aliyah “Salafiyah” Pasuruan, because of a limited appropriate matter for Arabic under this Islamic Boarding School. A process of adopting the matter from “Kitab Kuning” seems to be an urge for this school due to necessity order in linking students’ talent and interest to learn about Islamic Canon Laws in teaching Arabic related with reading skill. Research and Development method is used by the researcher to emerge a special product and to measure the product efficiency in 2nd grade of Madrasah Aliyah “Salafiyah” Pasuruan for extended period 1429 – 1430 M. Having some advices from Arabic teacher and an expert teaching method of Arabic for Madrasah Aliyah on this Islamic Boarding School support the adopting process of “Kitab Kuning” can be finished. The researcher intends to use the advices to fix the contents of her lesson matter. This lesson matter consists of Competency Standard, Integrated Standard Based Competency, Indicator Level and an assignment on every topic.Pre-test is given to the 2nd grade students of Aliyah in order to measure their reading skill before the researcher starts her own lesson matter product. And their results reach 68% or can be referred in middle standard (enough). Then, the researcher starts the process in conducting her own lesson matter for about two months. At the end of the program, post-test is used to see how well the students receive or understand the lesson matter and the students’ average score can be reached 88% or in the highest level. So, it means that this lesson matter product is extremely effective in developing students reading skill. The researcher suggests for the next research to conduct an observation on: (1) Arranging another appropriate lesson matter such as listening skill or speaking skill to this grade, (2) Conducting MA own book under the Islamic Boarding School internal system for the 3rd grade, (3) Exploration an interesting teaching method for MA, (4) Home base curriculum is deserved by the board internal. Key words: Preparing matter, “Kitab Kuning”, Reading Skill